LncRNAs and miRNAs participate in determination of sensitivity of cancer cells to cisplatin - Taheri, Mohammad; Shoorei, Hamed; Tondro Anamag, Farhad; Ghafouri-Fard, Soudeh; Dinger, Marcel E. (Experimental and molecular pathology, 2021)
Cisplatin is an extensively used chemotherapeutic substance for various types of human malignancies including sarcomas, carcinomas and lymphomas. Yet, the vast application of this drug is hampered by the emergence of chemoresistance in some treated patients. Several mechanisms such as degradation of the membrane transporters by cisplatin have been implicated in the pathogenesis of this event. Recent researches have also indicated the role of long non-coding RNAs (lncRNAs) as well as micoRNAs (miRNAs) in the emergence of resistance to cisplatin in several cancer types. For instance, up-regulation of miR-21 has been associated with resistance to this agent in ovarian cancer, oral squamous cell cancer, gastric malignancy and non-small cell lung cancer (NSCLC). On the other hand, down-regulation of miR-218 has been implicated in emergence of chemoresistance in breast cancer and esophageal squamous cell carcinoma. MALAT1 is implicated in the chemoresistance of bladder cancer cells, NSCLC, gastric cancer and cervical cancer. Most notably, the expression profile of resistance-associated miRNAs and lncRNAs can predict overall survival of cancer patients. Mechanistic assays have revealed that interference with expression of some miRNAs and lncRNAs can reverse the resistance phenotype in cancer cells. In this paper, we review the scientific writings on the role of lncRNAs and miRNAs in the evolution of chemoresistance to cisplatin in cancer cells.